(untitled) (Asian Journal of Social Science Studies, 2022)
With the popularization of computers and smart phones, the number of Internet users in China is increasing, and network technology is also developing. The resulting big data and related technologies have brought a series of economic benefits. However, there are some network platforms that only seek profits and ignore business ethics. They use big data to kill users. There are different opinions on the concept of big data in China. However, there is no doubt that the network platform using big data murder seriously violates the privacy of consumers, and causes consumers to suffer property losses, resulting in adverse social impact. Although there are many laws to protect citizens’ privacy in our country, there is still a dilemma of legal regulation for the infringement of citizens’ privacy by network platform and the use of big data. The reason is that big data as a new technology, the original law inevitably lags behind; moreover, due to its high technical requirements, ordinary citizens have great difficulties in perception and proof of big data familiarity killing due to information asymmetry.